ANALYSIS OF FACTORS TRAVELER BEHAVIOR WITH EXPLORATORY FACTOR ANALYSIS TO CHOOSE RESTAURANT AT AIRPORT - Almira Fitri, Rahmania
Tourism is an activity carried out individually or in groups from one place to another. Tourism is closely related to food. Food is one of the important activities during a tour, starting from when you go on a tour to being in a tourist spot. One of the modes of transportation most often used by tourists is airplanes. The airport is a facility for someone who is going to travel by plane. Places to eat or restaurants at the airport become an area that is often visited by airport users while waiting for flights. Places to eat at the airport are facilities used by airport users ranging from travelers traveling alone, with groups to tourist escorts. Types of places to eat at the airport are varied, ranging from light meals too heavy meals. The purpose of this study is to identify factors of tourist behavior in choosing where to eat when at the airport. This study uses literature studies derived from previous research, as well as journals and research related to the selection of places to eat. The method used in this study is Exploratory Factor Analysis (EFA) by distributing questionnaires to 200 respondents online and analyzed using data processing analysis factors using SPSS version 25 trial series tools. The results of this study are some factors influence travelers choosing where to eat at the airport. Based on the results of the analysis found eight factors that influence tourist behavior in choosing where to eat, including physical environmental factors, promotion and purchasing factors, social factors, service and payment information factors, factors of food type, culinary culture factors, dining conditions, and knowledge food.